Porcine enteric alphacoronavirus Inhibits IFN-α, IFN-β, OAS, Mx1, and PKR mRNA Expression in Infected Peyer's Patches in vivo - Xu, Zhichao; Gong, Lang; Peng, Peng; Liu, Yufang; Xue, Chunyi; Cao, Yongchang (Frontiers in Veterinary Science, 2020)
Porcine enteric alphacoronavirus (PEAV) is a newly identified swine enteropathogenic coronavirus that causes watery diarrhea in neonatal piglets. The pathogenesis and host immune responses of PEAV infection is not fully characterized. The obstacle lies in stomach environment which would degrade live viruses via oral infection, making it difficult to establish an effective infection model to study the pathogenesis and host immune responses in pigs with mature immune system. To solve the problem, in this study, coated PEAV-loaded microspheres were developed by centrifugal granulation-fluidized bed coating and demonstrated as an effective oral delivery system/animal infection model to protect PEAV virion against the complex gastrointestinal environment in vitro and to cause infection in weaned piglets. Weaned piglets orally inoculated with coated PEAV-loaded microspheres could develop diarrhea and virus RNA was detected in rectal swabs from 1 to 7 days post inoculation. Moreover, PEAV significantly inhibited mRNA expression of IFN-α, IFN-β, OAS, Mx1 and PKR, the genes involved in modulation of the host immune responses, in infected Peyer's patches, indicating that PEAV can overcome the innate immune responses to cause damage when infection occurs. Collectively, our research successful established a PEAV animal infection model in weaned piglets and suggested that the observed gene expression profile might help explain immunological changes associated with PEAV infection.